In-situ Monitoring of Side Friction of Drilled Piles by Different Loading Methods. (2016) - Zhang, Liqing; Ma, Ye; Song, Chunxia; Yang, Yu; Zhao, Lvyin
Abstract: Side frictions of three groups of drilled piles under different loading methods in Xinwan interchange of Qianjiang Passageway and Connecting Project were monitored. Group 1 was loaded by static loading test method. The other two groups were loaded by dead load of superstructures, which were constructed using segmental hanging basket method and overall support cast-in-place method respectively. Axial forces and Side friction in all the piles increased gradually during the load-adding procedure. Group 1 was loaded two months after the finish of pile foundation construction, while group 3 started bearing the action of superstructure dead load six months after the finish of pile foundation construction. Piles in Group 1 and Group 3 have different repose time. Side frictions monitored from piles in Group 3, which have longer repose time, were larger than those in Group 1 under the same load. Side frictions monitored from piles in Group 2, which have longer off-time between two loading stage, were larger than those in Group 1 under the same load.